2020
DOI: 10.21093/ijeltal.v5i1.574
|View full text |Cite
|
Sign up to set email alerts
|

Blended Learning Application in Higher Education: EFL Learners’ Perceptions, Problems, and Suggestions

Abstract: This study sought to explore Indonesian university students' perceptions, problems, and suggestions of the application of blended learning in their EFL courses. A questionnaire consisting of 6 categories (benefits of online learning, benefits of face-to-face learning, learning assessment, problems in blended learning, suggestions for quality improvement of blended learning, and open-ended questions) was used as the research instrument. The collected data were analyzed descriptively and qualitatively. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 28 publications
2
33
0
Order By: Relevance
“…These obstacles are the same as previous studies (Manurung et al, 2020) that EFL students had obstacles when learning hybrid: bad internet connection, slow feedback, confusing instruction; electrical instability and nervousness; and challenging learning materials. A good blended learning design must be providing clear learning instructions, be accessible at any time, assist in completing lessons, provide userfriendly features and comprehensive learning materials, clearly define learning objectives, and provide the necessary learning materials (Rianto, 2020). Therefore, the learning material on blended learning must have a clear indication for each topic, be defined in sufficient depth, provide a clear summary for each topic, include problemsolving examples and areas for online discussion, and provide a relationship between the indicators, content, and assignment.…”
Section: Discussionmentioning
confidence: 99%
“…These obstacles are the same as previous studies (Manurung et al, 2020) that EFL students had obstacles when learning hybrid: bad internet connection, slow feedback, confusing instruction; electrical instability and nervousness; and challenging learning materials. A good blended learning design must be providing clear learning instructions, be accessible at any time, assist in completing lessons, provide userfriendly features and comprehensive learning materials, clearly define learning objectives, and provide the necessary learning materials (Rianto, 2020). Therefore, the learning material on blended learning must have a clear indication for each topic, be defined in sufficient depth, provide a clear summary for each topic, include problemsolving examples and areas for online discussion, and provide a relationship between the indicators, content, and assignment.…”
Section: Discussionmentioning
confidence: 99%
“…Journal on English as a Foreign Language, 11(1), 152-174 p-ISSN 2088-1657e-ISSN 2502-6615 In Indonesia, few studies (Rerung, 2018;Rianto, 2020) showed students' positive attitudes towards blended learning. Rianto (2020) used a questionnaire to ask students' opinions of using a university e-learning system in their course.…”
Section: Introductionmentioning
confidence: 99%
“…Challenges in using digital tools in online learning, however, are evidenced in some studies. First, students' lack of IT knowledge (Holley & Oliver, 2010;Okaz, 2015), other technical issues, and insufficient network stability (Rerung, 2018;Rianto, 2020;Sari & Wahyudin, 2019;Yamin 2020), are challenges, which might hinder students from learning successfully. Moreover, there might be limited opportunities for the students to practice spoken communicative skills.…”
Section: Introductionmentioning
confidence: 99%
“…To face the change, integrating face-to-face learning (direct interaction) and technology-based learning (digital communication) becomes promising (Garrison &Vaughan, 2008;Rianto, 2020). Therefore, it is urgent to identify how the teachers and students were prepared to meet this new teaching and learning phase.…”
Section: Introductionmentioning
confidence: 99%
“…However, full e-learning did not give students a massive impact yet, and lately, they have become less motivated since it provided no real communication (Mese & Sevilen 2021). Integrating face-to-face learning (direct interaction) and technologybased learning (digital communication) becomes promising (Garrison &Vaughan, 2008;Rianto, 2020). This study explored the perspectives of 3 pre-service teachers and 27 students towards the blended learning (BL) practices in the EFL context.…”
mentioning
confidence: 99%